THE US-MEXICO BORDER: THE HISTORY OF SHAPING IN THE CONTEXT OF THE US CONTINENTAL EXPANSION IN THE XIX CENTURY - Tat’yana Pantyukhina (Гуманитарные и юридические исследования)
The paper features the history of shaping the state border between the USA and Mexico in the XIX century in the context of the US foreign policy as well as the history of colonization of the territories which now make up the borderland region of present-day Mexico and the USA. The main trend of American foreign policy in the XIX century was continental expansion. Pushing its boundaries westward, towards the Pacific, the USA confronted European powers which had their colonies on the continent. The first demarcation between Spanish colonies and the US territory was defined by the Treaty of 1819. Mexico, which won independence in 1821, inherited its borders with the USA from Spain. Nevertheless, Mexican borderland, Texas in particular, was a long standing objective of American expansionists. After annexation of Texas the US-Mexico border remained unspecified due to the fact that both countries claimed vast spaces between the Nueces and Rio Grande Rivers. The borderland dispute ignited 1846-1848 War, as a result of which the US gained over half Mexican territories. The Treaty of Guadalupe Hidalgo of 1848 defined the extended American border. The purchase of Mexican territory between Colorado and Rio Grande Rivers in 1853 completed the formation of the current US-Mexico border. Irrespective of belonging to either Mexico or the US the borderlands remained underpopulated till the middle of the XIX century. In fact, the territories were dominated by the Indians. After the military defeat of the Comanches and the Apaches in the 1870-80s the borderlands underwent rapid and radical demographic transformation. By the end of the XIX century the region changed from a zone dominated by indigenous people to a region totally controlled by a newly arrived non-Spanish Europeans.